SOME FAMOUS FOLKLORE CLAIMS OF GANDHAMARDAN HILL TRIBALS, NRUSINGHANATH, ODISHA - Mohanty, *SP; Rautaray, KT (International Journal of Ayurveda and Pharma Research, 2019)
The use of medicinal plants is a fundamental component of Indian traditional healthcare system. It is the oldest and most used health care system among all therapeutic systems. In many parts of India and specifically here in Odisha this traditional system of healing is the mainstay healthcare system. These undocumented but locally proven system has a potential for research for the benefit of human race which is all most at end point of contemporary healthcare system. The present article deals with the database usage of nearly 14 species of medicinal plants found around Gandhamardhan hills, Nrusinghnath forest areas in odisha and its important folklore claims.